Multi-dimensional self-esteem and magnitude of change in the treatment of anorexia nervosa. (30th March 2016) - Collin, Paula; Karatzias, Thanos; Power, Kevin; Howard, Ruth; Grierson, David; Yellowlees, Alex
Abstract: Self-esteem improvement is one of the main targets of inpatient eating disorder programmes. The present study sought to examine multi-dimensional self-esteem and magnitude of change in eating psychopathology among adults participating in a specialist inpatient treatment programme for anorexia nervosa. A standardised assessment battery, including multi-dimensional measures of eating psychopathology and self-esteem, was completed pre- and post-treatment for 60 participants (all white Scottish female, mean age=25.63 years). Statistical analyses indicated that self-esteem improved with eating psychopathology and weight over the course of treatment, but that improvements were domain-specific and small in size. Global self-esteem was not predictive of treatment outcome. Dimensions of self-esteem at baseline (Lovability and Moral Self-approval), however, were predictive of magnitude of change in dimensions of eating psychopathology (Shape and Weight Concern). Magnitude of change in Self-Control and Lovability dimensions were predictive of magnitude of change in eating psychopathology (Global, Dietary Restraint, and Shape Concern). The results of this study demonstrate that the relationship between self-esteem and eating disorder is far from straightforward, and suggest that future research and interventions should focus less exclusively on self-esteem as a uni-dimensional psychological construct. Highlights: Self-esteem improvements during the course of treatment are small in size. Self-esteem is not predictive of treatment outcome. Interventions focusing on self-esteem are not sufficient. Interventions should on self-esteem as a multi-dimensional construct.